Validation of Arylphosphorothiolates as Convergent Substrates for Ar-SF4Cl and Ar-SF5 Synthesis - Wang, Lin; Ni, Shengyang; Cornella, Josep (Synthesis, 2021)
In this manuscript we describe the oxidative fluorination of aryl phosphorothiolates to access Ar-SF4Cl compounds. These compounds serve as precursors for the highly coveted Ar-SF5 compounds. The use of phosphorothiolates as starting materials permits access to Ar-SF4Cl from a wide variety of available starting materials, namely boronic acids, diazonium salts, aryl iodides, thiophenols, or simple arenes. The protocol has been demonstrated for >10 examples and showed good tolerance to various functional groups. Finally, we demonstrated that AgBF4 can be used as a fluorinating agent, affording good yields of an Ar-SF5.
Keywords: fluorine; phosphorus; sulfur; pentafluorosulfanylation; isosteres